2010
DOI: 10.1093/bioinformatics/btq140
|View full text |Cite
|
Sign up to set email alerts
|

A CROC stronger than ROC: measuring, visualizing and optimizing early retrieval

Abstract: Motivation:The performance of classifiers is often assessed using Receiver Operating Characteristic ROC [or (AC) accumulation curve or enrichment curve] curves and the corresponding areas under the curves (AUCs). However, in many fundamental problems ranging from information retrieval to drug discovery, only the very top of the ranked list of predictions is of any interest and ROCs and AUCs are not very useful. New metrics, visualizations and optimization tools are needed to address this 'early retrieval' prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 17 publications
0
124
0
Order By: Relevance
“…Paired t -tests 54 indicated that the neural network and the logistic regressor were statistically equivalent for both average pair AUC ( p -value 0.339) and top-two ( p -value 0.286). To break the tie, we constructed reliability plots, which quantify how well predictions correlate to probabilities (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paired t -tests 54 indicated that the neural network and the logistic regressor were statistically equivalent for both average pair AUC ( p -value 0.339) and top-two ( p -value 0.286). To break the tie, we constructed reliability plots, which quantify how well predictions correlate to probabilities (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…However, both the pair-level neural network and the pair-level logistic regressor significantly improved performance compared to only training on the atom-level, especially by the top-two metric. For example, comparing the top-two performances of the pair-level logistic regressor and the atom-level neural network by a paired t -test 54 yielded a p -value of 0.037. Consequently, we retained the pair-level training and model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the training set, performance with respect to recovery of the actives (top 10 inhibitors) was analyzed in a statistical manner [24][25][26][27] .…”
Section: Statistical Analysis Of Docking Performancementioning
confidence: 99%
“…Through a simulation study and analysis of real microarray data, they show that the difference is considerable. Swamidass et al [25] propose the concentrated ROC framework in which any relevant portion of the ROC curve is magnified smoothly by an appropriate continuous transformation. The area under the ROC curve assesses retrieval performance of the relevant portion.…”
Section: Comparing L > 2 Algorithms On M > 1 Data Setsmentioning
confidence: 99%